The Beneficial Effects of ETS-GS, a Novel Vitamin E Derivative, on a Rat Model of Crush Injury. Issue 6 (December 2016) - Nakagawa, Junichiro; Matsumoto, Naoya; Nakane, Yuko; Yamakawa, Kazuma; Yamada, Tomoki; Matsumoto, Hisatake; Shimazaki, Junya; Imamura, Yukio; Ogura, Hiroshi; Jin, Takashi; Shimazu, Takeshi
Abstract : ABSTRACT: Crush syndrome is a devastating condition leading to multiple organ failure. The mechanisms by which local traumatic injuries affect distant organs remain unknown. ETS-GS is a novel water-soluble, stable anti-oxidative agent composed of vitamin E derivative. Given that one of the main pathophysiological effects in crush syndrome is massive ischemia-reperfusion, reactive oxygen species (ROS) generated from the injured extremities would be systemically involved in distant organ damage. We investigated whether ETS-GS could suppress inflammatory response and improve mortality in a rat model of crush injury. Crush injury was induced by compression of bilateral hindlimbs for 6 h followed by release of compression. Seven-day survival was significantly improved by ETS-GS treatment. To estimate anti-oxidative and anti-inflammatory effects of ETS-GS, serum was collected 6 and 20 h after the injury. ETS-GS treatment significantly dampened the up-regulation of malondialdehyde and reduction of superoxide dismutase in the serum, which were induced by crush injury. Serum levels of interleukin 6 and high mobility group box 1 were significantly decreased in the ETS-GS group compared with those in the control group. Lung damage shown by hematoxylin-eosin staining at 20 h after the injury was ameliorated by the treatment. Ex vivo imaging confirmed that ETS-GS treatment reduced ROS generation in both the lung and the muscle following crush injury. The administration of ETS-GS could suppress ROS generation, systemic inflammation, and the subsequent organ damage, thus improving survival in a rat model of crush injury. These findings suggest that ETS-GS can become a novel therapeutic agent against crush injury.